Implementation of Punishment in the Formation of Student Attitudes in Madrasah Tsanawiyah: a Case Study of a Tourism-Based Community in North Sumatra Indonesia - Nurul Arsih; Hemawati Hemawati (The Islamic Education and Multiculturalism Foundation, 2026)
Abstract Praktik hukuman edukatif dalam pendidikan Islam terus menjadi isu penting karena madrasah dituntut menegakkan disiplin tanpa mengabaikan martabat dan perkembangan psikologis peserta didik. Persoalan ini menjadi semakin kompleks di Madrasah Tsanawiyah Bukit Lawang, Kabupaten Langkat, Sumatera Utara, yang berada di kawasan ekowisata internasional dengan paparan nilai sosial dan budaya yang sangat beragam. Penelitian ini bertujuan menganalisis implementasi hukuman dalam pembentukan sikap siswa, menelaah pengaruh lingkungan pariwisata terhadap pergeseran nilai, serta mengevaluasi efektivitas hukuman berdasarkan prinsip pedagogi Islam. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi yang melibatkan kepala madrasah, guru bimbingan dan konseling, guru pendidikan agama Islam, dan siswa dari beberapa tingkat kelas. Analisis data menggunakan model interaktif Miles dan Huberman melalui reduksi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Hasil penelitian menunjukkan bahwa hukuman diterapkan secara bertahap mengikuti tujuh tahapan pedagogis Abdullah Nasih Ulwan, mulai dari nasihat, teguran, isyarat nonverbal, hingga sanksi edukatif dan keagamaan. Hukuman yang dilaksanakan secara adil, penuh kasih sayang, dan konsisten terbukti memperkuat kesadaran normatif, rasa tanggung jawab, serta perubahan perilaku siswa, sehingga berfungsi sebagai instrumen kontrol moral dan sosial yang efektif dalam menjaga identitas keagamaan madrasah. Kata kunci: Punishment; Sikap Siswa; Pendidikan Islam; Madrasah; Komunitas Pariwisata Abstract Educational punishment in Islamic schooling remains a critical issue because madrasahs are expected to enforce discipline without undermining students’ dignity and psychological development. This challenge becomes more complex at Madrasah Tsanawiyah Bukit Lawang, Langkat Regency, North Sumatra, which is located in an international ecotourism area marked by intensive exposure to diverse social and cultural values. This study aims to analyze the implementation of punishment in shaping student attitudes, examine the influence of the tourism environment on value shifts, and evaluate the effectiveness of punishment through the lens of Islamic pedagogy. The study employed a qualitative case study design. Data were collected through participant observation, semi-structured interviews, and documentation involving the madrasah principal, guidance and counseling teachers, Islamic education teachers, and students from several grade levels. Data were analyzed using Miles and Huberman’s interactive model through data reduction, data display, and conclusion drawing and verification. The findings reveal that punishment is implemented in stages according to Abdullah Nasih Ulwan’s seven pedagogical phases, ranging from advice, reprimands, and nonverbal cues to educative and religious sanctions. When administered with justice, compassion, and consistency, punishment strengthens students’ normative awareness, sense of responsibility, and behavioral change, allowing it to function as an effective instrument of moral and social control while preserving the madrasah’s religious identity. Keywords: Punishment; Student Attitudes; Islamic Pedagogy; Madrasah; Tourism Community